The effect of gravity and inclined load in micropolar thermoelastic medium possessing cubic symmetry under G-N theory - Mohamed I.A. Othman; S.M. Abo-Dahab; Haneen A. Alosaimi (Journal of Ocean Engineering and Science, 2018)
The problem of the micropolar thermoelastic medium under (G-N) theory of both types II, III under the effect of the gravity was investigated. The normal mode analysis is used to obtain the solution of the physical quantities. Comparisons are made between the results predicted by the (G-N) theory of type II and type III in the presence and absence of gravity and for different values of the angle of inclination. Keywords: Micropolar thermoelasticity, Green-Naghdi theory, Normal mode method, Gravity, Inclined load